(untitled) (Nigerian Journal of Physiological Sciences, 2025)
In this study, we compared the ulcer healing effect of carbohydrate-, protein- and fat-rich diets on acetic acid-induced ulcers in young and aged rats. Male Wistar rats (40 each at 3-, 6-, 12-, and 18 months old) were grouped into four to receive basal diet (control), carbohydrate-, protein-, or fat-rich diets for 21 days before acetic acid-induced gastric injury. After this, the various feedings continued for 3- and 7 days. Planimetry was used for the ulcer healing study. We estimated the redox status, pepsin, mucin, and nitric oxide activities by UV/Vis-spectrophotometer while the Epidermal Growth Factor-Receptor (EGF-R) was by immunohistochemistry. Data was analyzed (two-way ANOVA) and was considered significant at p≤0.05. Percentage ulcer healing by day 7 relative to day 3 decreased with advancing age in other diets but increased in the aged rats fed a protein-rich diet. Gastric carbonyl, Malondehyde, and pepsin activities increased significantly with age, while superoxide dismutase, catalase, mucin, Nitric-oxide and EGF-R expression significantly decreased with age. Protein-rich diets modulated the age-related alterations. These findings suggest that a protein-rich diet facilitates the healing of acetic acid-induced gastric injury by enhancing gastroprotective activity to favour EGF-R expression in the ulcerated stomach